Ubiquitous Computing - Gestures Interaction Applied the Learning Disabilities in Process Literacy - Oliveira, Danielle Teixeira; Carvalho, Marla Dore; Paixão, Tuane Lisboa Silva (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2016)
This article uses the interaction of gestures and learning concept with mobility or mobile learning (M-Learning) to propose a mobile platform based on manipulation gestures focusing on benefit children in the literacy process in early childhood education to submit a learning disability. Based on ubiquitous computing and better usability, the objective is to make children can learn while playing through the manipulation of objects in touchscreen